Cervicocephalic Spotty Calcium for the Prediction of Coronary Atherosclerosis in Patients With Acute Ischemic Stroke - Zheng, Chong; Yan, Shaozhen; Fu, Fan; Zhao, Cheng; Guo, Daode; Wang, Zhichao; Lu, Jie (Frontiers in Neurology, 2021)
Purpose: To investigate the characteristics of cervicocephalic spotty calcium (SC) and coronary atherosclerosis in patients with acute ischemic stroke (AIS) and to assess the predictive value of SC for coronary atherosclerosis using combined coronary and cervicocephalic CTA. Materials and Methods: Patients with AIS (n = 70) confirmed by brain MRI or CT and patients with asymptomatic carotid atherosclerosis (n = 58) confirmed by carotid ultrasonography were enrolled in our study. Subjects in both groups underwent combined coronary and cervicocephalic CTA. SC was used to evaluate cervicocephalic atherosclerosis. Coronary artery stenosis (CAS) ≥ 50% by segment and coronary artery calcium score (CACS) were used to evaluate coronary atherosclerosis. The SC frequency and the difference in coronary atherosclerosis between the two groups were compared, and the correlation between SC and coronary atherosclerosis was analyzed. Independent factors for CAS ≥ 50% were assessed via logistic regression analysis. Receiver operating characteristic curve analysis was performed to evaluate the added value of SC for predicting CAS ≥ 50%. Results: Both SC and the CACS were significantly higher in the Stroke group than in the Control group (total SC count: 6.83 ± 4.34 vs. 2.98 ± 2.87, P < 0.05; CACS: 477.04 ± 798.01 vs. 136.31 ± 205.65, P < 0.05). There were significant differences in the presence of CAS ≥ 50% (61.4 vs. 27.6%, P < 0.001). SC and coronary atherosclerosis were significantly correlated for both the CACS and CAS ≥ 50% (r = 0.746 and 0.715, respectively; P < 0.001). SC was an independent predictor for CAS ≥ 50%. Conclusion: SC correlates significantly with the CACS and could serve as an independent predictor of CAS ≥ 50% in patients with AIS, which suggests that combined cerebrovascular and cardiovascular assessments are of importance for such patients.